Carbamazepine and Cognitive Impairment - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
Members of the Departments of Pediatrics, Neurology, and Clinical Pharmacology and Toxicology at the Children's Hospital and Ohio State University, Columbus, OH 43205, assessed neuropsychological function before and after carbamazepine monotheraphy at low ( <-7.5,ug/ml) and moderate (>8.0,ug/ml) plasma levels in 11 children (4 boys 7 girls, mean age 9.8 yrs) with controlled complex partial epilepsy.